(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
This article presents a wave energy converter exploiting the pitch of a floating body moored to the seabed. When the floating body tilts under the action of an incoming wave, a movable mass, placed inside the hull, moves relative to the floating body and actuates an electrical generator. Most devices of this type have the drawback that the moving mass sequentially accelerates, slows down, stops and then repeats this sequence in the opposite direction. This generates an irregular instantaneous power output. The proposed concept consists of (at least) two eccentric bodies having the same mass and revolving at opposite speeds around a vertical axis. In this « counterrotating » solution, the oscillations of the float result in the continuous circular motion of the direct-drive PTO, though the global centre of gravity of the eccentric bodies moves back-and-forth along the symmetry axis of the device. If the eccentric bodies move at constant speed, their global centre of gravity moves in a sinusoidal manner along its pathway. The present study aims to investigate, through modelling and numerical simulations, the influence of the main parameters, such as the phase and the PTO mass moment, on the performance of a counter-rotating device exposed to waves of various heights and various wavelengths. Optimal phase and mass moment are determined numerically. The resulting output power is close to the theoretical maximum power that can be harvested by the floating body.